Desingning User Experience Folklore Book Application with Design Thinking Method (Case Study of Malin Kundang Story) - Nur Handoko*, Thalia Maharani; Persada, Andhika Giri (Universitas Syiah Kuala, 2023)
Folklore has an important role in children's development because it introduces moral and ethical values that can shape children's character and introduce Indonesian culture and traditions. However, folklore today is less in demand by children. The design of storybook applications that have good reusability is expected to increase children's interest in reading folklore. Therefore, it is necessary to design a folklore book application that uses Design Thinking. The method used in the development of the user experience of the folklore book application